2022
DOI: 10.3390/s23010247
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Applications of Random Lasers as Emerging Light Sources and Optical Sensors: A Review

Abstract: In a random laser (RL), optical feedback arises from multiple scattering instead of conventional mirrors. RLs generate a laser-like emission, and meanwhile take advantage of a simpler and more flexible laser configuration. The applicability of RLs as light sources and optical sensors has been proved. These applications have been extended to the biological field, with tissues as natural scattering materials. Herein, the current state of the RL properties and applications was reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 165 publications
1
7
0
Order By: Relevance
“…RL emission performance of HNT1 and HNT2 is expected to be identical because of their similar linear optical properties around ∼600 nm. Anyway, inhomogeneity in the distribution of the scatterer may lead to a slight improvement in the P in Th , as we have observed for HNT1-RhB.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…RL emission performance of HNT1 and HNT2 is expected to be identical because of their similar linear optical properties around ∼600 nm. Anyway, inhomogeneity in the distribution of the scatterer may lead to a slight improvement in the P in Th , as we have observed for HNT1-RhB.…”
Section: Resultssupporting
confidence: 52%
“…The characteristics and performance of RL emission are comparable to the recently reported colloidal disordered system containing an artificially designed 2D material as passive scatterers, paving the way to multiple applications of HNT-based RLs, such as speckle-free imaging, 31 medical diagnostics, anticounterfeiting. 50,57 In addition, HNTs are a cheap and abundantly available nanomaterial suitable for a true mass-scale industrial application, 24 HNTs with peculiar morphology, purity, and size distribution, 9 and compared to other nanotubular particles such as carbon nanotubes, for halloysite clay, the world supply is in the range of 50,000 tons/year. 24 In perspective, the anisotropic shape of HNTs, which are morphologically similar to nanowires and nanotubes, may pave the way for further developments.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various perovskite lasers, random lasers (RLs) have drawn attention due to their unique properties, for example, low spatial coherence, which can effectively eliminate speckles in laser imaging. , RLs are based on the light scattering/reflection in the gain medium to form random cavities, which enable lasing emission without predesigned cavities, allowing RLs to be a facile and promising random number generator in all-optical computing. , Furthermore, such a randomly distributed feedback mechanism in RLs is sensitive to changes in local environmental conditions, allowing RLs to be useful for sensing applications. , Therefore, thermally evaporated perovskite RLs can be a promising on-chip light source for all-optical application.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Furthermore, such a randomly distributed feedback mechanism in RLs is sensitive to changes in local environmental conditions, allowing RLs to be useful for sensing applications. 41,42 Therefore, thermally evaporated perovskite RLs can be a promising on-chip light source for all-optical application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the fourteenth, paper by Ni et al [ 14 ], the authors demonstrated the applicability of random lasers as light sources and optical sensors. In a random laser (RL), optical feedback arises from multiple scattering instead of conventional mirrors.…”
mentioning
confidence: 99%